Quodammodo transfiguratum est in animum: Erasmus' doctrine of the resurrection of the body and its Origenian roots - Fallica, Maria (Zeitschrift für antikes Christentum, 2019)
The paper addresses Erasmus' doctrine of the resurrection of the body in relationship with its Origenian inheritance, its polemical context and the general hermeneutical attitude of Erasmus. The mind-body dualism and the Platonism of Erasmus' doctrine are better understood in relation to Origen's Pauline doctrine of the resurrected body. A passage particularly revealing of this Origenian reception, in a mystical direction, is the conclusion of Erasmus' masterpiece, the Praise of Folly. Through this text, the paper aims to clarify Erasmus' concept of resurrection as transfiguration, from the letter to the spirit.